Rozwody wśród młodych dorosłych na tle innych grup wiekowych w świetle danych zastanych. Analiza zjawiska = Divorce among young adults compared to other age groups in the light of existing data. Analysis of the phenomenon - Oleszak, Milena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article examines the topic of divorce among young adults compared to other age groups in the light of existing data. The author analyzes the phenomenon. On the one hand, the discussed topic covers macro-processes which generate divorces, i.e. industrialization and urbanization; on the other hand, divorce is a matter of individual choice, resulting from the adopted value system. The question arises about the scale of this phenomenon among young adults. What causes such choices? In Poland, the number of divorces had been increasing till 2006, and since then has been slightly dropping.
Keywords: rozwód; młodzi dorośli; przyczyny rozwodów; system wartości; życie małżeńsko-rodzinne; divorce; young adult; divorce causes; value system; married and family life